A systematic review of Community Engagement (CE) in Disaster Early Warning Systems (EWSs). (January 2020) - Sufri, Sofyan; Dwirahmadi, Febi; Phung, Dung; Rutherford, Shannon
Abstract: Engaging the community in Early Warning Systems (EWSs) plays an essential role in saving lives, reducing injuries, and limiting environmental damage associated with disaster events. However, EWSs have traditionally focused on technology and infrastructure with the absence of comprehensive engagement with the community across the four EWS elements of risk knowledge, monitoring, dissemination and communication and response capability. Subsequently, past experience shows inappropriate responses by communities during disasters. This study reviews definitions, concepts and evolution of EWSs, and the applicability of Community Engagement (CE) in EWSs. It aims to systematically review how the community is engaged in the four elements of EWSs using evidence from the literature sourced from peer-reviewed articles and grey literature. From a total of 4211 initial documents sourced from 2008 to 2018, 31 documents (15 peer-reviewed journal articles and 16 grey literature from project reports) were finally selected to review after an extensive screening process. Of the 31 documents, most of them were from Low- and Middle-Income Countries (LMICs) especially the Asian region, followed by the African region. The findings indicate inadequate CE across the four EWS elements (dominating in the risk knowledge element with a single hazard focus). Identified key issues included challenges for sustainability of CE in EWSs, inadequate integration of local and scientific knowledge into EWS design and operation and insufficient consideration of the full range of vulnerable groups in the system. More systematic and sustained efforts are required to improve CE in all EWS elements in order to achieve more effective disaster response.